Gene expression and protein distribution of ADAMTSL-4 in human iris, choroid and retina. Issue 9 (11th July 2013) - Chandra, Aman; Jones, Megan; Cottrill, Phillippa; Eastlake, Karen; Limb, G Astrid; Charteris, David G
Abstract : Background: Mutations in ADAMTSL4 have recently been shown to be the major cause of autosomal recessive isolated ectopia lentis (IEL). However, the function and ocular localisation of the protein is yet to be fully established. We therefore aimed to confirm the expression of this gene and protein in normal ocular tissue. Methods: Donor ocular tissue was obtained within 48 h post-mortem and iris, choroid and retina were isolated for analysis. Expression of mRNA coding for ADAMTSL4 was examined in four eyes using reverse transcription PCR. Protein coding for this molecule was also investigated in two eyes by western blot analysis. Furthermore, the in situ localisation of ADAMTSL4 was investigated in cryostat sections of whole eyes following immunostaining for this protein and confocal analysis of the stained tissue. Results: mRNA and protein coding for ADAMTSL4 were both demonstrated to be expressed in iris and choroidal tissue but were absent from the neural retina. Confocal studies revealed ADAMTS-Like 4 to be present in the ciliary body and ciliary processes and also in the retinal pigment epithelium. Conclusions: We have confirmed the gene and protein expression of ADAMTSL4 in human ocular tissue. The pattern of expression may suggest further functions of this gene beyond those suggested by its causative role in IEL.